Possibility of Peroxidation Process Correction in Ratâ€™s Organism at Cold Stress - Petrun, L. M. (Problems of Cryobiology and Cryomedicine, 2008)
Intensity of lipid peroxidation in thymus rat enzymatic fraction at cold stress (4Â°C) was investigated. It was shown that with small doses of polyamines it was possible to decrease peroxidation processes of an organism.